Nine keys to world-class business process outsourcing - Lacity, Mary Cecelia; Willcocks, Leslie (Bloomsbury, 2015)
"Business Process Outsourcing (BPO)-- the sourcing of business services through external third parties--is a global phenomenon, which generated nearly $300 billion worldwide in 2012. BPO is highly IT-enabled, and on a growth trajectory that impacts across functions of major, medium and small enterprises, including procurement, human resources, accounting and finance, sales, marketing, legal, asset management and key administrative processes. Despite this size and spread, BPO services and the ability of clients to manage their providers, are still evolving and have a mixed record. In the course of their research, the authors have found only 20% of outsourcing arrangements are world-class performers. A further 25% are 'good', 40% are 'OK' and 15% are 'poor'. This book pinpoints and describes in detail the effective practices that characterize the top global BPO performers, including Microsoft, BP, EMC and TalkTalk. The authors provide case illustrations and examples throughout of how world-class practices were generated and evolved, and how they can be applied to real life settings and problem areas."--Bloomsbury Publishing